Volume 2A: Turbomachinery 2019
DOI: 10.1115/gt2019-91253
|View full text |Cite
|
Sign up to set email alerts
|

Loss Analysis of Unsteady Turbomachinery Flows Based on the Mechanical Work Potential

Abstract: Loss analysis is a valuable technique for improving the thermodynamic performance of turbomachines. Analysing loss in terms of the ‘mechanical work potential’ (Miller, R.J., ASME Turbo Expo 2013, GT2013-95488) provides an instantaneous and local account of the thermal and aerodynamic mechanisms contributing to the loss of thermodynamic performance. This study develops the practical application of mechanical work potential loss analysis, providing the mathematical formulations necessary to perform loss analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In the case of averaging without using common parameters before the cascade, the "history" of the flow is not taken into account, and only the parameters of the initial non-uniform flow are averaged in different ways [1][2][3][4][5][6]. In [2] determines axisymmetric flow, which is averaged through surfaces and meridian streamlines, [3] performs averaging based on mechanical work potential, [4] uses Favre-averaged Fourier-based methods with application to gas turbines, [5,6] also uses averaging techniques to evaluate turbomachine efficiency. A significant variety of gas flow averaging methods raises the question of their effectiveness and allows you to combine different approaches to improve their performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of averaging without using common parameters before the cascade, the "history" of the flow is not taken into account, and only the parameters of the initial non-uniform flow are averaged in different ways [1][2][3][4][5][6]. In [2] determines axisymmetric flow, which is averaged through surfaces and meridian streamlines, [3] performs averaging based on mechanical work potential, [4] uses Favre-averaged Fourier-based methods with application to gas turbines, [5,6] also uses averaging techniques to evaluate turbomachine efficiency. A significant variety of gas flow averaging methods raises the question of their effectiveness and allows you to combine different approaches to improve their performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, euergy appears well-suited to examining turbomachinery flow as it has been derived from the same thermodynamic process to which turbomachines aspire -a reversible adiabatic expansion. To the author's knowledge, this method has only previously been applied by Blackburn & Miller 2.3 Modelling loss mechanisms in turbomachinery (2017) to examine pressure gain combustion and Leggett et al (2019) to examine unsteady compressor flow.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the companion paper, the comparison against experiments showed that the RANS simulation is well able to recover the flow physics due to the strong influence of free-stream turbulence. However, several recent papers have shown that a detailed discussion of losses (entropy generation) can be better performed by LES [18,20,21,24] . In addition, the SLES turb.inj.…”
Section: Exergy Analysis In the Simulation Domainmentioning
confidence: 99%
“…Lower levels of turbulence modelling are obtained for LES approach compared to RANS [38,39] that may expect a better resolution of the flow field at the interface between cavity and main annulus flow. From a loss perspective, recent studies have shown that the assessment of loss in a gas turbine can be obtained more accurately by LES compared to RANS [18,20] , this being due to a better resolution of turbulent field that drives the mixing process of momentum and enthalpy which in turns controls the level of losses generated in the flow field [35] . This paper uses the exergy formalism to draw the loss generated in a low-speed linear cascade with an upstream cavity including a parametric study of the purge flow rate supplied to the cavity and the rim seal geometry.…”
Section: Introductionmentioning
confidence: 99%